2021
DOI: 10.1016/j.heliyon.2021.e07066
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated lung on contrast-enhanced chest CT: the use of spectral-detector computed tomography parameters in differentiating atelectasis and pneumonia

Abstract: Spectral CT parameters C iodine and Z eff can differentiate atelectasis from pneumonia on contrast-enhanced images. Spectral CT parameters C iodine and Z eff have no added value compared to CT number measurement on CON 120kVp images. CNRs between normal and consolidated lung were higher on conventional on spectral images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This is similar to what has been described in human radiology for discriminating atelectatic lung from pneumonia. 24 Comparison between necropsy and PMCTA…”
Section: Pathology On Pmctamentioning
confidence: 99%
“…This is similar to what has been described in human radiology for discriminating atelectatic lung from pneumonia. 24 Comparison between necropsy and PMCTA…”
Section: Pathology On Pmctamentioning
confidence: 99%
“…High X-ray attenuation in CT scans is observed in lungs of the most severe patients with COVID [23] or pneumonia [24]. X-ray attenuation is measured in Hounsfield Units (HU).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [17,[19][20][21] have demonstrated that chest CT is also of high value in the prognosis of PQ poisoning, while the optimal indicator remains unclear. Computed tomography (CT) number, also known as the Hounsfeld Unit, is a relative quantitative measurement of x-ray density [22]. It is the most frequently used quantitative CT parameter and widely used in radiological diagnosis, attenuation correction, and radiotherapy treatment planning [23].…”
Section: Introductionmentioning
confidence: 99%